2015
DOI: 10.1071/rdv27n1ab323
|View full text |Cite
|
Sign up to set email alerts
|

323 Estrogen-Induced Epithelial-Mesenchymal Transition and Expression of Proapoptotic Markers in Porcine Stem Cells

Abstract: In transgenic pig production for generating animal models of human diseases, apoptosis of early implantation embryo disturbs the transgenic pig production. In general, epithelial-mesenchymal transition (EMT) is considered important in embryo development and apoptosis. In addition, it was reported that 17β-oestradiol (E2), among hormones that participate in early implantation of embryo, could induce EMT and neural differentiation in mouse embryonic stem cells. Therefore, in this study, we examined the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The EMT mechanism, proved to be effective for the metastatic niche creation, was found to play a pivotal role in embryo development and implantation too (18). Recently, Kim et al (56) using a porcine animal model, elucidate the underlying mechanism of EMT that was found to be controlled by steroid hormones. Besides to the action integrins-mediated, POSTN can directly interact with the other ECM proteins.…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 99%
See 2 more Smart Citations
“…The EMT mechanism, proved to be effective for the metastatic niche creation, was found to play a pivotal role in embryo development and implantation too (18). Recently, Kim et al (56) using a porcine animal model, elucidate the underlying mechanism of EMT that was found to be controlled by steroid hormones. Besides to the action integrins-mediated, POSTN can directly interact with the other ECM proteins.…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 99%
“…Since experimental data found that the activation of EMT programs in epithelial cells correlates with the appearance of stemness, authors suggested that the EMT process also leads the initial cancer cell colonization at distant sites (56). It is quite obvious that EMT reverse program, also called MET, is required for efficient metastatic colonization (56). As a matter of fact, EMT allows cancer cells to increase their motility and invasiveness properties allowing these cells to leave the primary epithelial tumor site.…”
Section: Recently Postn Has Proven To Be the Key Protein In The Metamentioning
confidence: 99%
See 1 more Smart Citation